Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22031323
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronate Causes a Systemic Shift of Macrophage Polarization towards M1 In Vivo

Abstract: Background: Immunomodulatory properties of bisphosphonates (BP) are suggested to contribute to the development of medication-associated osteonecrosis of the jaw (MRONJ). Furthermore, bisphosphonate-derived immune modulation might contribute to the anti-metastatic effect observed in breast cancer patients. Macrophages are potential candidates for the mediation of immunomodulatory effects of bisphosphonates. The study aimed to investigate the influence of bisphosphonates alone and in combination with surgical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“… 51 Furthermore, a seminal study by Weber and colleagues demonstrated that Zol alone and in combination with surgical trauma significantly increased infiltration and shifted systemic macrophage polarization toward M1 type in spleen, lung, and skin of Wister rat model. 52 All these studies provide additional evidence of Zol contributing towards modulation of the immune system. PDAC is very difficult to treat and resistant to most conventional therapies due to dense stromal meshwork and immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 85%
“… 51 Furthermore, a seminal study by Weber and colleagues demonstrated that Zol alone and in combination with surgical trauma significantly increased infiltration and shifted systemic macrophage polarization toward M1 type in spleen, lung, and skin of Wister rat model. 52 All these studies provide additional evidence of Zol contributing towards modulation of the immune system. PDAC is very difficult to treat and resistant to most conventional therapies due to dense stromal meshwork and immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 85%
“…Several hypotheses have been raised regarding the transformation of existing chronic in ammatory lesions into MRONJ, and an M1 macrophage shift is considered the most likely explanation. Kang Osteonecrosis occurs when BP or RANKL inhibitors are administered in the presence of in amed pulpal or periodontal tissue, because anti-resorptive agents affect the function of various immune cells, such as of neutrophils and polymorphonuclear leukocytes, macrophages, and dendritic cells [21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…mediated M1/M2 macrophage alteration is related to the development of BRONJ23 , Tamaki et al reported that dynamic M1/M2 macrophage polarization was induced by the anti-RANKL antibody in a MRONJ model31 , while Weber et al analyzed MRONJ in Wistar rats and found that zoledronate induces a macrophage M1 shift24 .Human studies on macrophage function in this context have also been performed. For instance, Hoefert et al reported that patients with MRONJ had a compromised macrophage function when compared to patients with osteoradionecrosis and osteomyelitis25 , and Paschalidi et al found M1/M2 macrophage polarization in macrophages of patient tissues in MRONJ, and that macrophages shift to the M1 phenotype at stages 2 and 3, as compared to stage 1 of MRONJ 26 .…”
mentioning
confidence: 99%
“…Золедроновая кислота также усиливала местное раздражающее действие ксеногенного матрикса, выражающееся в повышенной эозинофилии и фиб розировании области трансплантации. Согласно полученным ранее данным, подобный эффект мог быть следствием приобретения макрофагами фенотипа M1 под влиянием золедроновой кислоты [36], что привело к дисбалансу поляризации макрофагов между провоспалительным (М1) и противовоспалительным (М2) фенотипами, а в результате -к активизации регуляторной функции эозинофилов и локальному фиброзу.…”
Section: таблица 6 нежелательные явления отмеченные в экспериментальн...unclassified